Antibacterial activity on methicillin-resistant Staphylococcus aureus (MRSA) and antioxidant properties of silver nanoparticles synthesized by Hunteria umbellata (K. Schum.) seeds - Fidelis Ifeakachukwu OKOLAFOR; Martyna Chinedu UBA; Onoche Vera OKOLAFOR; Salem Kivos ADEBIYI (Studia Universitatis Babeș-Bolyai. Biologia)
Silver nanoparticles (AgNPs) have gained significant attention over the years due to their unique physicochemical properties and diverse applications in various areas including medicine, electronics, and so on. Hunteria umbellata (HU), is a glabrous tree native to West Africa that belongs to the Apocynaceae family with various medicinal properties. The medicinal applications; anti-microbial and anti-oxidant properties of synthesized and characterized silver nanoparticles by using HU seeds, were studied. Aqueous and ethanol extracts of HU were obtained for the synthesis process. UV-Vis spectra analysis was used to reveal the distinct absorption patterns for AgNPs synthesized by ethanol and aqueous extracts. FTIR spectra exhibited characteristic transmittance peaks, indicating the presence of functional groups such as hydroxyl groups. XRD analysis confirmed the crystalline nature of AgNPs with identifiable peaks at specific planes while SEM/EDX was used to provide insights into the size distribution and morphology of AgNPs, reinforcing the data from other characterization methods. Medicinal properties were assessed through antibacterial assays using Methicillin-Resistant Staphylococcus aureus (MRSA) and DPPH radical scavenging activity, showcasing the potential biomedical applications of AgNPs-HU complex. Comparative studies with standard compounds like ascorbic acid validated their efficacy as antioxidants. The findings of this study suggest promising antibacterial and antioxidant properties of AgNPs-HU complex synthesized by HU seeds extracts and also contribute to the understanding of nanomedicine and underscore the potential of green synthesis for biomedical applications.